Effect of Novel Feed Additive on Egg Production and Blood Parameters of Hens during Post-Peak Production - Pratama, Anugrah Robby; Sugiharto, Sugiharto (Jurnal Agripet, 2023)
ABSTRACT. The present study evaluated the effect of feed additives containing Averrhoa bilimbi L. fruit filtrate, wheat bran, and Saccharomyces cerevisiae on egg production and blood parameters of laying hens during post-peak production. The experiment was carried out according to a completely randomized design with 224 hens (80 weeks old). The hens were randomly distributed to 4 treatments and 7 replications. The treatments included T0 (basal feed), T1 (basal feed + 0.25% additive), T2 (basal feed + 0.5% additive), T3 (basal feed + 1% additive). Feed intake was recorded daily, body weight was determined weekly, and blood was collected on day 35 of the experiment. The variables measured included feed intake, feed conversion ratio, hen day production, egg weight, yolk index, albumin index, eggshell thickness, yolk color, and complete blood counts. Results showed that hen-day production decreased (P0.05) as the level of additives increased in the feed. Dietary inclusion of additive at 0.25% increased (P0.05) eggshell thickness. The feed conversion ratio tended (P=0.08) to be better in hens receiving additives at 0.25%. Compared to control, additive at 0.5% decreased (P0.05) red blood cell distribution width-standard deviation (RDW-SD) and red blood cell distribution width-coefficient variation (RDW-CV) of laying hens. In conclusion, novel feed additives containing A. bilimbi L. fruit filtrate, wheat bran, and S. cerevisiae, particularly at 0.25% of the diet improved hen day egg production, eggshell thickness, and feed conversion ratio.(Pengaruh novel feed additive terhadap produksi telur dan parameter darah ayam petelur pasca puncak produksi)ABSTRAK. Penelitian ini mengevaluasi pengaruh imbuhan pakan yang mengandung filtrat buah belimbing wuluh, dedak gandum dan S. cerevisiae terhadap produksi telur dan parameter darah ayam petelur selama pasca produksi puncak. Penelitian dilaksanakan berdasarkan rancangan acak lengkap (RAL) menggunakan 224 ekor ayam petelur (umur 80 minggu). Ayam-ayam tersebut didistribusikan ke 4 kelompok perlakuan dan 7 ulangan. Perlakuan tersebut meliputi T0 (pakan basal), T1 (pakan basal + aditif 0,25%), T2 (pakan basal + aditif 0,5%), T3 (pakan basal + aditif 1%). Konsumsi pakan dicatat setiap hari, bobot badan ditimbang setiap minggu dan darah diambil pada hari ke-35 penelitian. Parameter yang diamati dalam penelitian meliputi konsumsi pakan, rasio konversi pakan, produksi telur harian, berat telur, indeks kuning telur, indeks albumin, ketebalan cangkang telur, warna kuning telur dan profil darah lengkap. Hasil penelitian menunjukkan bahwa hen day production menurun (P0,05) seiring dengan peningkatan level aditif dalam pakan. Aditif pakan pada level 0,25% meningkatkan ketebalan cangkang telur (P0,05). Rasio konversi pakan cenderung lebih baik (P=0,08) pada ayam petelur yang menerima aditif sebesar 0,25%. Dibandingkan dengan kontrol, aditif 0,5% menurunkan RDW-SD dan RDW-CV (P0,05) ayam petelur. Sebagai kesimpulan, imbuhan pakan yang mengandung filtrat buah belimbing wuluh, dedak gandum dan S. cerevisiae khususnya pada level 0,25% meningkatkan produksi telur ayam, ketebalan cangkang telur dan rasio konversi pakan.